ZHENIZHOK’S LYRICAL SONGS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In this article,in addition to works related to the “Aitysh” genre, philosophical and lyrical aspects of such works as “Dunuyo”, “Nakyl”, “Ait, ait dese”, “Akkan suu”, “Zhalgyz tal”, “Balam jok”, and “Koksuluu” are analyzed, and akyn’s views on life are also considered fate and nature, proving the weight and scale of his views. In his work, akyn Zhenizhok mastered the technique of writing poetic lines at a high level, convincingly emphasizing his skill in artistic word writing.
Keywords: folklore, poem, legend, rhyme, rediff, alliteration, akyn, nature, lircs.